Determination of Static and Dynamic Yield Stress of Chengdu Clay Slurry - XianJun, Ji; Ying, Liang; WenHao, Cao; XiaoKang, Sun; Peng, Song (Frontiers in Physics, 2022)
The yield stress of mud is one key to analyze the initiation and deposition of debris flow. Taking Chengdu clay as the experimental material, slurries with different solid volume concentrations were prepared. Using the blade rotor system of mcr301 rheometer and the continuous shear experimental method, the dynamic change process of shear stress of slurries with different solid volume concentrations was obtained with the shear rate increasing and decreasing continuously. According to the experimental results, the static and dynamic yield stress of Chengdu clay slurry is determined, and the influence of solid volume concentration on the yield stress is analyzed. The following conclusions are obtained: Chengdu clay slurry is a non-Newtonian fluid with yield stress. In the process of accelerated shear, for Chengdu clay slurry with solid volume concentration exceeding 35%, the shear rate is in the range of 0.01–1 s−1, and the shear stress increases rapidly to the maximum. When the shear rate exceeds 1 s−1, the shear stress decreases rapidly and finally tends to be stable. The shear rate appears stress overshoot near 1s−1. However, in the process of increasing shear rate, for Chengdu clay slurry with solid volume concentration of no more than 35%, the shear stress increases rapidly in the range of shear rate of 0.01–0.1 s−1, and the shear rate exceeds 0.1 s−1. The shear rate has little effect on the shear stress, and the stress overshoot disappears. In the process of deceleration shear, for all solid volume concentrations in the semi logarithmic coordinate system, the mud shear stress decreases steadily with the decrease of shear rate. The static and dynamic yield stress of slurry increases exponentially with particle concentration.